Understanding the Investment Behavior of Millennial Certified Public Accountants (CPA) in General Santos City - Quisil, Rodel D.; Salise, Kerby P. (International Journal of Research in Interdisciplinary Studies, 2025)
It examines the investment behavior of millennial Certified Public Accountants (CPAs) in General Santos City, Philippines, focusing on how financial financial capability in terms of financial knowledge, financial attitude, and financial stability influence their investment decisions. The research uses a quantitative, descriptive-correlational design, with survey questionnaires distributed to 83 millennial CPAs. By analyzing the demographic and investment profiles of the respondents, the study aims to understand how these factors impact investment frequency, risk management, portfolio diversification, and overall investment decision-making. The findings highlight the challenges young professionals face in making informed and disciplined investment choices, despite their strong financial knowledge. The study also provides recommendations for enhancing financial education and encouraging responsible investment practices, contributing to the development of strategies that promote long-term wealth-building among millennials.